My fair frauds : a novel - Kelly, Lee; Thorne, Jennifer, 1980- (Harper Muse, 2025)
"A high society fraud and a scrappy swindler team up to take down Gilded Age New York in this tale of intrigue, drama, and female friendship"-- Provided by publisher.